Carcass wrote:
If \(r > 0\), s ≠ \(\frac{1}{2}\) and \(r = \frac{3s +1}{1-2s}\), then \(s=\)
A) \(\frac{3r}{12 +6r}\)
B) \(\frac{-2r}{3}\)
C) \(\frac{r-1}{3+2r}\)
D) \(\frac{2}{3(1-r)}\)
E) \(\frac{-1+r}{3}\)
Given: \(r = \frac{3s +1}{1-2s}\)
Multiply both sides by (1 - 2s) to get: r(1 - 2s) = 3s + 1
Expand: r - 2rs = 3s + 1
NOTE: We want the s's on one side. So....
Add 2rs to both sides: r = 3s + 2rs + 1
Subtract 1 from both sides: r - 1 = 3s + 2rs
Factor right side: r - 1 = s(3 + 2r)
Divide both sides by (3 + 2r) to get: (r - 1)/(3 + 2r) = s
Answer:
Cheers,
Brent